2020
DOI: 10.3389/fonc.2020.00594
|View full text |Cite
|
Sign up to set email alerts
|

Physician Attitudes and Perceptions of Complementary and Alternative Medicine (CAM): A Multicentre Italian Study

Abstract: Purpose: Complementary and Alternative Medicine (CAM) interventions are widely used by patients with chronic disorders, including cancer, and may interact with cancer treatment. Physicians are often unaware of this, probably due to poor patient-physician communication on CAM. The purpose of this study was to evaluate physicians' knowledge, attitudes and practice patterns regarding CAM in a survey conducted in Italy.Methods: A questionnaire was administered to 438 physicians (11 Italian hospitals) who predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 81 publications
5
44
0
Order By: Relevance
“…14 While conventional practitioners are encouraged to work with CIM practitioners when the patient chooses CIM therapies as part of their lung cancer treatment regimen, the majority of such practitioners receive little to no training in CIM. 15 , 16 This can discourage communication between the patient and clinician regarding CIM, thereby creating barriers in the treatment plan. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 While conventional practitioners are encouraged to work with CIM practitioners when the patient chooses CIM therapies as part of their lung cancer treatment regimen, the majority of such practitioners receive little to no training in CIM. 15 , 16 This can discourage communication between the patient and clinician regarding CIM, thereby creating barriers in the treatment plan. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 This can discourage communication between the patient and clinician regarding CIM, thereby creating barriers in the treatment plan. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…This approach could be particularly relevant in tumors difficult to treat due to pharmacological resistance, which is fostered by different molecular mechanisms. Complementary and alternative medicine (CAM) is largely believed to present an integrative role within conventional therapy even in the context of cancer therapy, sustaining natural products employment [ 132 , 133 , 134 , 135 , 136 ]. Resveratrol represents a highly promising dietary phytochemical, with interesting properties in the context of different pathologies, including cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary and alternative medicines (CAM) are natural bioactives with anti-inflammatory, anticancer and chemo preventive properties. Several clinical trials demonstrated the safe and useful of CAM in cancer patients (79)(80)(81)(82). Polydatin, also called piceide, is a metabolite of trans-resveratrol, a natural bioactive isolated from the perennial herb Polygonum cuspidatum (83), with interesting properties in the field of cancer, cardiovascular diseases, neurodegenerative disorders (84,85).…”
Section: Discussionmentioning
confidence: 99%